Moderasi Beragama Sebagai Upaya Membangun Kerukunan dalam Masyarakat Multikultural - Pikhy Ardiansyah; Darussalam Syamsuddin; Lomba Sultan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Religious moderation has become an increasingly important discourse in contemporary society due to the growing challenges of intolerance, radicalism, and social polarization in religious life. In a multicultural and multi-religious context, the implementation of religious moderation is essential for maintaining social harmony and fostering peaceful coexistence among different communities. This article aims to examine the concept of religious moderation, analyze its fundamental principles, and explore its implementation in promoting interreligious harmony. The study employs a qualitative approach through library research by analyzing relevant literature, including books, academic journals, government publications, and Islamic sources related to religious moderation. The findings reveal that religious moderation is characterized by a balanced and middle-path approach in understanding and practicing religion, grounded in principles such as tawassuth (moderation), tawazun (balance), tasamuh (tolerance), i‘tidal (justice), and musawah (equality). Furthermore, the implementation of these principles contributes significantly to strengthening social cohesion, encouraging mutual respect among religious communities, and preventing extremist attitudes. The study concludes that religious moderation serves as a strategic framework for fostering religious harmony and social stability in diverse societies. This research contributes to the field of religious and social studies by providing a conceptual understanding of religious moderation and highlighting its relevance in addressing contemporary challenges related to interfaith relations and social integration.